Method for recycling and regenerating lithium iron phosphate into sodium battery positive electrode material
Through steps such as ball milling activation and low-temperature sintering, waste lithium iron phosphate materials are regenerated into sodium battery cathode materials, which solves the problems of poor consistency of recycled materials and waste of lithium ions, and achieves sodium battery cathode materials with high structural stability and cycle stability. The preparation is suitable for large-scale application.
Patent Information
- Application Number
- CN202411569015.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-11-05
AI Technical Summary
The prior art has problems such as poor consistency, the use of a large amount of inorganic acids to remove impurities and waste of lithium ions when recycling lithium battery lithium iron phosphate.
By sintering the abolition of the lithium iron phosphate material with the phosphorus source and the iron source, the front -drive body LIXFE3 (PO4) 2 (P2O7) is obtained, and then mixed with the sodium source in the restore atmosphere for low -temperature sintering to achieve Li+/NA+ion exchange exchange exchange With the reaction reaction, the sodium electrode material NA4-Aliafe3 (PO4) 2 (P2O7) with high structure stability and cycle stability was obtained through washing and low temperature heat treatment.
This method can effectively solve the problem of poor consistency of recycling materials and waste of lithium ion, and prepare sodium electrode materials with low composite or miscellaneous content, high ionic conductivity, good appearance, and improve the battery's multiplier performance and long performance and length Cycle stability, low cost, suitable for large -scale applications.
Smart Images

Figure CN119349539A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery material recycling, and specifically relates to a method for preparing a sodium battery positive electrode material with high structural stability and cycle stability from waste lithium iron phosphate materials. Background Art
[0002] The development of new energy vehicles and other industries has led to a rapid growth in the demand for lithium / sodium-ion batteries, and with it comes the problem of recycling a large number of waste lithium / sodium-ion batteries. Waste lithium / sodium-ion batteries contain high-value metal elements such as lithium, nickel, cobalt, manganese, aluminum, and copper, as well as organic electrolytes and plastics that seriously threaten the safety of the ecological environment. Therefore, the recycling of waste lithium / sodium-ion batteries has considerable economic and environmental benefits.
[0003] At present, the recycling methods of lithium iron phosphate positive electrode materials for lithium batteries include solid phase method, inorganic acid leaching precipitation, etc. The solid phase method adds a lithium source to the waste lithium iron phosphate material for roasting and repairing. However, the composition of the recycled battery materials is uneven, and the difference in raw materials causes poor consistency of the recycled battery materials; inorganic acid leaching obtains iron-phosphorus filter residues through liquid phase leaching filtration, and finally obtains iron phosphate by adjusting the pH. However, this method currently uses a large amount of inorganic acid in the leaching process, which causes difficulties for subsequent impurity removal when introducing excessive acid radical ions. At the same time, lithium ions are not recycled, resulting in waste of lithium ions and increasing the difficulty of subsequent wastewater treatment. Therefore, how to efficiently recycle lithium iron phosphate positive electrode materials for lithium batteries is a major challenge faced by technicians in this field.
[0004] CN115259125A discloses a method for recycling lithium iron phosphate recycled materials, wherein the lithium iron phosphate material is obtained by pretreatment with hydrogen peroxide and subsequent lithium supplementation and roasting. However, the problem that the lithium content in the lithium iron phosphate recycled materials fluctuates greatly and the lithium supplementation process is difficult has not been solved.
[0005] CN115312897A reports a method for repairing waste lithium iron phosphate and the obtained lithium iron phosphate material, wherein the waste lithium iron phosphate is degummed to obtain lithium iron phosphate recovery material; the lithium iron phosphate recovery material is mixed with a reducing agent, a lithium source is added, and the reaction is carried out in a fluidized bed reactor so that the lithium iron phosphate and the lithium source are fully mixed and contacted, thereby achieving a sufficient lithium supplementation effect, and at the same time, a carbon source is sprayed in the high-temperature filtration of the second stage to form a carbon-coated structure on the surface of the lithium iron phosphate, so that the repaired lithium iron phosphate is separated from the excess lithium source. However, this method has complicated steps and strict requirements on equipment, and cannot be applied on a large scale. Summary of the invention
[0006] In response to the above technical problems, the present application provides a method for regenerating waste lithium iron phosphate materials into sodium battery positive electrode materials.
[0007] To achieve the above objectives, this application proposes the following solutions: In a first aspect, a method for recycling lithium iron phosphate into a sodium positive electrode material is provided, comprising: S1. After ball milling and activation of waste lithium iron phosphate material, phosphorus source and iron source, sintering is performed to obtain precursor Li x Fe3(PO4)2(P2O7), where 0.8≤x≤1; S2, after the sodium source and the precursor are mixed evenly, low temperature sintering is performed in a reducing atmosphere to achieve Li + / Na + Ion exchange and reduction reaction to obtain bulk material; S3, washing the bulk material to remove impurity ions, and then performing solid-liquid separation, drying and low-temperature heat treatment to obtain the sodium positive electrode material Na 4-a Li a Fe3(PO4)2(P2O7), where the value of a is 0~0.3.
[0008] In a second aspect, a sodium positive electrode material is provided, wherein the chemical formula of the sodium positive electrode material is Na 4-a Li a Fe3(PO4)2(P2O7), wherein the value of a is 0~0.3, is prepared by the aforementioned preparation method.
[0009] In a third aspect, a sodium ion battery is provided, comprising the aforementioned sodium battery positive electrode material.
[0010] Compared with the prior art, one or more of the above technical solutions can achieve at least one of the following beneficial effects: Waste lithium iron phosphate cathode material is activated by ball milling, crystal transformation, reduction and Li + / Na + Exchange, low temperature heat treatment, regeneration to prepare sodium positive electrode material Na with high structural stability and cycle stability 4-a Li a Fe3(PO4)2(P2O7) solves the problems of long recycling process and high cost of conventional lithium iron phosphate batteries, and also solves the problems of Na 4- a Li a Fe3(PO4)2(P2O7) materials are prone to the problem of impurity phase.
[0011] This recycling and regeneration method can prepare sodium battery positive electrode materials that are free of impurities or have low impurity content, high ionic conductivity, and good morphology, thereby improving the battery's rate performance and long-cycle stability.
[0012] This recycling method is low-cost and has been widely promoted and applied. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0014] Figure 1 The present invention is a process flow chart for recycling lithium iron phosphate into sodium battery positive electrode material.
[0015] Figure 2 This is the SEM image of the lithium iron phosphate material obtained in Example 1.
[0016] Figure 3 This is the XRD test result of the sodium battery positive electrode material obtained in Example 1.
[0017] Figure 4 This is the electrochemical cycle data diagram of the battery assembled with the sodium cathode material obtained in Example 1.
[0018] Figure 5 This is the electrochemical rate data diagram of the battery assembled with the sodium cathode material obtained in Example 1.
[0019] Figure 6 This is the electrochemical cycle data diagram of the battery assembled with the sodium cathode material obtained in Example 2.
[0020] Figure 7 This is the electrochemical rate data diagram of the battery assembled with the sodium cathode material obtained in Example 2.
[0021] Figure 8 This is the XRD test result of the sodium battery positive electrode material obtained in Comparative Example 1.
[0022] Fig. 9 This is a partially enlarged view of the XRD detection results of the sodium battery positive electrode material obtained in Example 1.
[0023] Fig.10 This is a partially enlarged view of the XRD test results of the sodium battery positive electrode material obtained in Comparative Example 1.
[0024] Fig.11 This is the electrochemical cycle data diagram of the battery assembled with the sodium cathode material obtained in Comparative Example 1.
[0025] Fig.12 This is the electrochemical rate data diagram of the battery assembled with the sodium cathode material obtained in Comparative Example 1.
[0026] Fig.13This is the electrochemical cycle data diagram of the battery assembled with the sodium cathode material obtained in Example 3.
[0027] Fig.14 This is the electrochemical rate data diagram of the battery assembled with the sodium cathode material obtained in Example 3.
[0028] Fig.15 This is the electrochemical cycle data diagram of the battery assembled with the sodium cathode material obtained in Example 4.
[0029] Fig.16 This is the electrochemical rate data diagram of the battery assembled with the sodium cathode material obtained in Example 4. DETAILED DESCRIPTION
[0030] The present invention provides a method for recycling lithium iron phosphate into a sodium battery positive electrode material, comprising: S1. After ball milling and activation of waste lithium iron phosphate material, phosphorus source and iron source, sintering is performed to obtain precursor Li x Fe3(PO4)2(P2O7), where 0.8≤x≤1; S2, after the sodium source and the precursor are mixed evenly, low temperature sintering is performed in a reducing atmosphere to achieve Li + / Na + Ion exchange and reduction reactions to obtain bulk materials; S3, washing the bulk material to remove impurity ions, and then performing solid-liquid separation, drying and low-temperature heat treatment to obtain the sodium positive electrode material Na 4-a Li a Fe3(PO4)2(P2O7), wherein a is 0~0.3, and more preferably 0~0.25, for example, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, etc.
[0031] In some preferred embodiments, in step S1, the rotation speed of the ball milling activation is 100-200 rpm, for example, 100 rpm, 125 rpm, 150 rpm, 175 rpm, 200 rpm, etc.
[0032] In some preferred embodiments, in step S1, the ball milling activation time is 0.5 to 3 h, for example, 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, etc.
[0033] In some preferred embodiments, in step S1, the sintering temperature is 300-550°C, for example, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, etc.; the sintering time is 5-12h, for example, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, etc.
[0034] In some preferred embodiments, the phosphorus source is one or more of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, ammonium phosphate, lithium dihydrogen phosphate, sodium pyrophosphate, and ammonium pyrophosphate.
[0035] In some preferred embodiments, the iron source is one or more of ferric nitrate and its hydrate, ferric oxide, ferric phosphate, ferrous oxide, ferric hydroxide, and ferric pyrophosphate.
[0036] In some preferred embodiments, the waste lithium iron phosphate material is lithium iron phosphate black powder.
[0037] In some preferred embodiments, the waste lithium iron phosphate material, the phosphorus source and the iron source are prepared in a molar ratio of Li to total Fe and total P of 0.8 to 1:3:4, for example, 0.8:3:4, 0.82:3:4, 0.85:3:4, 0.88:3:4, 0.9:3:4, 0.92:3:4, 0.95:3:4, 1:3:4, etc.
[0038] In some preferred embodiments, in step S2, the temperature of the low-temperature sintering is 300-550°C, and the temperature of the low-temperature sintering is higher than the melting point of the sodium source, for example, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, etc.; the time of the low-temperature sintering is 1-15h, for example, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, etc.
[0039] In some preferred embodiments, in step S2, the reducing atmosphere is a mixed atmosphere of argon and hydrogen.
[0040] In some preferred embodiments, the ratio of the molar amount of Na contained in the sodium source to the molar amount of the precursor is 5 to 10:1, for example, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, etc.
[0041] In some preferred embodiments, the sodium source is one or more of sodium acetate and its hydrate, nitrate and its hydrate, carbonate and hydroxide. Preferably, the sodium source is a mixed sodium salt, which can reduce the melting point and thus reduce the temperature of low-temperature sintering. For example, a mixed sodium salt of sodium nitrate, sodium chloride and sodium carbonate can be used. The sodium nitrate, sodium chloride and sodium carbonate can be matched in a molar ratio of 0.92:0.064:0.016, or other ratios can be used.
[0042] In some preferred embodiments, in step S3, the temperature of the low-temperature heat treatment is 300~550℃, for example, 300℃, 350℃, 400℃, 450℃, 500℃, 550℃, etc.; the time of the low-temperature heat treatment is 5~12h, for example, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, etc.; the atmosphere of the low-temperature heat treatment is a protective gas atmosphere.
[0043] In some preferred embodiments, in step S2, the mixing is grinding mixing; the grinding mixing is mechanical grinding or manual grinding; the manual grinding time is 0.5 to 2 hours, and the manual grinding is carried out under vacuum or protective atmosphere; the mechanical grinding is grinding for 0.5 to 2 hours after adding a dispersant.
[0044] The present invention also provides a sodium positive electrode material, the chemical formula of which is Na 4-a Li a Fe3(PO4)2(P2O7), wherein the value of a is 0~0.3, and more preferably 0~0.25, for example, 0.01, 0.03, 0.05, 0.08, 0.10, 0.12, 0.15, 0.18, 0.20, 0.22, 0.25, etc., and is prepared by the aforementioned preparation method.
[0045] The present invention also provides a sodium ion battery, comprising the aforementioned sodium positive electrode material.
[0046] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the specification, but the protection scope of the present invention is not limited to the following specific embodiments.
[0047] Example 1 The method of recycling lithium iron phosphate into sodium battery positive electrode material, the process flow is as follows Figure 1 As shown, the following steps are included: (1) Take 1.6g of LiFePO4 black powder material, 3.45g of ammonium dihydrogen phosphate, and 8.08g of ferric nitrate nonahydrate (the molar ratio of lithium, iron, and phosphorus in the raw materials is 0.98:3:4 after testing), and perform ball milling activation in a ball mill at a speed of 200rpm for 0.5h. Then, the mixed powder is sintered in an air atmosphere in a tubular furnace to obtain a black powder precursor Li x Fe3(PO4)2(P2O7), sintering temperature is 400℃, time is 5h.
[0048] (2) Sodium source and black powder precursor were weighed according to a sodium to precursor molar ratio of 6:1, placed in a mortar, and manually ground for 1 h in a glove box filled with argon. The sodium source was a mixed sodium salt of sodium nitrate, sodium chloride and sodium carbonate (the molar ratio of NaNO3:NaCl:Na2CO3 was 0.92:0.064:0.016). The mixed material was placed in an argon hydrogen furnace, and Ar / H2 mixed gas was introduced. The temperature was raised to 350°C at a rate of 5°C / min, sintered for 8 h, and cooled with the furnace.
[0049] (3) The obtained block material was dissolved in deionized water and stirred for 20 minutes, then centrifuged at a speed of 5000 r / min, each centrifugation time was 7 minutes, and a total of 4 centrifugations were performed. The material was then placed in a blast drying oven for drying at a temperature of 80° C. for 15 hours to obtain a powder material.
[0050] (4) The powder material was heat treated in an argon atmosphere furnace at a temperature of 300°C for 5 hours to obtain a sodium positive electrode material. The SEM image of the obtained sodium positive electrode material is shown in Figure 2 shown. Figure 2 The results show that the material is composed of blocky primary particles agglomerated into spherical secondary particles, and the secondary particles still remain spherical. The optimization of this morphology can reduce the formation of microcracks in the material, reduce the intrusion of electrolyte during the material cycle, reduce the generation of microcracks, and improve the material's cycle performance and service life. The XRD pattern of the obtained sodium cathode material is shown in Figure 2. Figure 3 As shown, the XRD pattern shows that the generated sodium battery positive electrode material phase is Na4Fe3(PO4)2(P2O7) phase.
[0051] Table 1 shows the ICP test results of the Na4Fe3(PO4)2(P2O7) phase material obtained in Example 1. The data show that in Li + / Na + The material obtained by heat treatment after exchange contains only about 0.21wt.% Li + , the material contains 14.05wt.% Na + , proving that the target material Na 4-a Li aFe3(PO4)2(P2O7).
[0052] Table 1 The sodium positive electrode material obtained in this example is assembled into a button cell, and the specific steps are as follows: According to the mass ratio (active material: conductive agent: binder = 8:1:1), 0.08g of positive electrode material was weighed, and 0.01g of acetylene black as a conductive agent and 0.01g of polyvinylidene fluoride as a binder were weighed, placed in a mortar and mixed. After mixing evenly, N-methylpyrrolidone was added as a dispersant. After mixing again, the mixture was coated on aluminum foil to make a positive electrode sheet. In a glove box under an inert protective atmosphere, metallic lithium was used as the negative electrode to assemble a CR2032 button battery.
[0053] Figure 4 is the Na obtained in Example 1 4-a Li a The electrochemical cycle data of the battery assembled from Fe3(PO4)2(P2O7) materials shows that the battery still has a discharge capacity of 89 mAh / g after 300 cycles, and the cycle retention rate is as high as 98%.
[0054] Figure 5 is the Na obtained in Example 1 4-a Li a The electrochemical rate data of the battery assembled from Fe3(PO4)2(P2O7) material shows that the battery still has a discharge capacity of 78 mAh / g at an ultra-high rate of 5C, showing extremely high potential in the field of fast charging and discharging. Example 2 This embodiment includes the following steps: (1) Take 1.6 g of LiFePO4 black powder material, 3.45 g of ammonium dihydrogen phosphate, and 8.484 g of ferric nitrate nonahydrate (the molar ratio of lithium iron to phosphorus in the raw materials is 0.98:3.1:4 after testing), and perform ball milling activation in a ball mill at a speed of 200 rpm for 0.5 h. Then, the mixed powder is sintered in a tubular furnace to obtain a black powder precursor at a sintering temperature of 400 ° C for 5 h.
[0055] (2) Weigh the sodium source and black powder precursor according to the molar ratio of sodium to precursor of 8:1, put them into a mortar, and grind them manually in a glove box filled with argon for 1 hour. The sodium source is a mixed sodium salt of sodium nitrate, sodium chloride, and sodium carbonate (the molar ratio of NaNO3:NaCl:Na2CO3 is 0.92:0.064:0.016). Place the mixed material in an argon hydrogen furnace, introduce Ar / H2 mixed gas, heat to 400℃ at a rate of 5℃ / min, sinter for 8 hours, and cool with the furnace.
[0056] (3) The block material was dissolved in deionized water and stirred for 20 minutes, then centrifuged at a speed of 5000 r / min, each centrifugation time was 7 minutes, and a total of 4 centrifugations were performed. It was then placed in a blast drying oven for drying at a temperature of 80°C for 15 hours to obtain a powder material.
[0057] (4) The powder material is heat treated in an argon furnace at a temperature of 300°C for 5 h to obtain a positive electrode material.
[0058] The obtained positive electrode material was assembled into button-type batteries according to the method for assembling batteries in Example 1, and the electrochemical performance was tested.
[0059] Figure 6 This is an electrochemical cycle data diagram of a button cell assembled with the positive electrode material obtained in Example 2. The data show that after 300 cycles, the battery has a discharge capacity of only 76 mAh / g, and a cycle retention rate of only 93%.
[0060] Figure 7 This is an electrochemical rate data diagram of a button cell assembled with the positive electrode material obtained in Example 2. The data show that at an ultra-high rate of 5C, the battery has a discharge capacity of only 67 mAh / g.
[0061] Comparative Example 1 (1) Take 1.212 g of LiFePO4 black powder material and 1.2 g of sodium persulfate and add them to 70 ml of deionized water. Heat the reaction in a water bath at 80°C for 2 h to perform oxidative delithiation.
[0062] (2) The solution was centrifuged at a speed of 5000 r / min, each centrifugation time was 7 min, and the total number of centrifugations was 4. The solution was then dried in a forced air drying oven to obtain a black powder (the molar ratio of Li:Fe:P was about 0.072:0.976:1 according to the test results), the temperature was 80°C, and the drying time was 15 h.
[0063] (3) Weigh 0.9048 g of the black powder obtained in (2), 0.2254 g of diammonium hydrogen phosphate, 0.424 g of sodium carbonate, and 0.3568 g of glucose, and mill them in a ball mill at a speed of 200 rpm for 0.5 h to obtain a powder material.
[0064] (4) The powder material is heat treated in an argon hydrogen furnace by introducing an Ar / H2 mixed gas at a temperature of 550°C for 10 hours, and then cooled in the furnace to obtain a sodium positive electrode material.
[0065] The XRD pattern of the obtained sodium cathode material is shown in Figure 8As shown in the XRD diagram, it can be seen that the obtained sodium positive electrode material contains the phase Na4Fe3(PO4)2(P2O7), but the diffraction peak also shows the presence of impurity peaks. In order to further compare the sodium positive electrode material obtained in Example 1 with the sodium positive electrode material obtained in Comparative Example 1, Figure 3 and Figure 8 Perform local magnification respectively, such as Fig. 9 and 10 As shown, compared Fig. 9 and Fig.10 It can be seen that Fig.10 It is shown in Figure 2 that there are obvious impurity peaks at 33° and 35°. This indicates that after the lithium iron phosphate is first oxidized and delithiated, and then sintered with the sodium source and phosphorus source in a corresponding ratio, the resulting Na4Fe3(PO4)2(P2O7) contains impurity sodium iron phosphate.
[0066] The obtained positive electrode material was assembled into button-type batteries according to the method for assembling batteries in Example 1, and the electrochemical performance was tested.
[0067] Fig.11 This is the electrochemical cycle data diagram of the button battery assembled with the positive electrode material obtained in Comparative Example 1. The data show that after 300 cycles, the battery has a discharge capacity of only 68 mAh / g and a cycle retention rate of only 84%.
[0068] Fig.12 This is an electrochemical rate data diagram of a button cell assembled with the positive electrode material obtained in Comparative Example 1. The data show that at an ultra-high rate of 5C, the battery has a discharge capacity of only 62 mAh / g.
[0069] Example 3 The method of recycling lithium iron phosphate into sodium battery positive electrode material, the process flow is as follows Figure 1 As shown, the following steps are included: (1) Take 1.6 g of LiFePO4 black powder material, 3.45 g of ammonium dihydrogen phosphate, and 8.08 g of ferric nitrate nonahydrate (the molar ratio of lithium iron to phosphorus is 0.98:3:4 after testing), and perform ball milling activation in a ball mill at a speed of 200 rpm for 0.5 h. Then, the mixed powder is sintered in an air atmosphere in a tubular furnace to obtain a black powder precursor at a sintering temperature of 450 ° C for 5 h.
[0070] (2) Weigh a sodium source and a black powder precursor with a sodium-to-lithium molar ratio of 6:1, put them into a mortar, and grind them manually in a glove box filled with argon for 1 hour. The sodium source is a mixed sodium salt of sodium nitrate, sodium chloride, and sodium carbonate (NaNO3:NaCl:Na2CO3 molar ratio is 0.92:0.064:0.016). Place the mixed material in an argon-hydrogen furnace, introduce Ar / H2 mixed gas, heat to 400℃ at a rate of 5℃ / min, sinter for 8 hours, and cool with the furnace.
[0071] (3) The block material was dissolved in deionized water and stirred for 20 minutes, then centrifuged at a speed of 5000 r / min, each centrifugation time was 7 minutes, and a total of 4 centrifugations were performed. It was then placed in a blast drying oven for drying at a temperature of 80°C for 15 hours to obtain a powder material.
[0072] (4) The powder material is heat treated in an argon furnace at a temperature of 300°C for 5 hours to obtain a sodium positive electrode material.
[0073] Table 2 shows the ICP test results of the materials obtained in Example 3. The data show that in Li + / Na + The material obtained by heat treatment after exchange contains only about 0.19wt.% Li + , the material contains 14.07wt.% Na + , proving that the target material was successfully synthesized.
[0074] Table 2 The obtained positive electrode material was assembled into button-type batteries according to the method for assembling batteries in Example 1, and the electrochemical performance was tested.
[0075] Fig.13 is the Na obtained in Example 3 4-a Li a The electrochemical cycle data of the button battery assembled with Fe3(PO4)2(P2O7) material shows that after 300 cycles, the battery still has a discharge capacity of 84.5 mAh / g, and the cycle retention rate is as high as 97.8%.
[0076] Fig.14 is the Na obtained in Example 3 4-a Li a The electrochemical rate data of the button cell assembled with Fe3(PO4)2(P2O7) material shows that at the ultra-high rate of 5C, the battery still has a discharge capacity of 72 mAh / g, showing great potential in the field of fast charging and discharging.
[0077] Example 4 The method of recycling lithium iron phosphate into sodium battery positive electrode material, the process flow is as follows Figure 1 As shown, the following steps are included: (1) Take 1.6g of LiFePO4 black powder material, 3.45g of ammonium dihydrogen phosphate, and 8.08g of ferric nitrate nonahydrate (the molar ratio of iron to phosphorus is 0.98:3:4 after detection), and perform ball milling activation in a ball mill at a speed of 200rpm for 0.5h. Then, the mixed powder is sintered in an air atmosphere in a tubular furnace to obtain a black powder precursor at a sintering temperature of 500℃ for 5h.
[0078] (2) Weigh a sodium source and a black powder precursor with a sodium-to-lithium molar ratio of 10:1, put them into a mortar, and grind them manually for 1 hour in a glove box filled with argon. The sodium source is a mixed sodium salt of sodium nitrate, sodium chloride, and sodium carbonate (the molar ratio of NaNO3:NaCl:Na2CO3 is 0.92:0.064:0.016). Place the mixed material in an argon-hydrogen furnace, heat it to 400°C at a rate of 5°C / min, sinter it for 8 hours, and cool it in the furnace.
[0079] (3) The block material was dissolved in deionized water and stirred for 20 minutes, then centrifuged at a speed of 5000 r / min, each centrifugation time was 7 minutes, and a total of 4 centrifugations were performed. It was then placed in a blast drying oven for drying at a temperature of 80°C for 15 hours to obtain a powder material.
[0080] (4) The powder material is heat treated in an argon furnace at a temperature of 400°C for 5 hours to obtain a sodium positive electrode material.
[0081] Table 3 is the ICP test results of the materials obtained in Example 4. The data show that in Li + / Na + The material obtained by heat treatment after exchange contains only about 0.21wt.% Li + , the material contains 14.05wt.% Na + , proving that the target material was successfully synthesized.
[0082] Table 3 The obtained positive electrode material was assembled into button-type batteries according to the method for assembling batteries in Example 1, and the electrochemical performance was tested.
[0083] Fig.15 is the Na obtained in Example 4 4-a Li a The electrochemical cycle data of the button battery assembled with Fe3(PO4)2(P2O7) material shows that after 300 cycles, the battery still has a discharge capacity of 84.3 mAh / g, and the cycle retention rate is as high as 97.7%.
[0084] Fig.16 is the Na obtained in Example 44-a Li a The electrochemical rate data of the button cell assembled with Fe3(PO4)2(P2O7) material shows that at the ultra-high rate of 5C, the battery still has a discharge capacity of 72.3 mAh / g, showing great potential in the field of fast charging and discharging.
[0085] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for recycling lithium iron phosphate into sodium positive electrode material, characterized in that: include: S1. After ball milling and activation of waste lithium iron phosphate material, phosphorus source and iron source, sintering is performed to obtain precursor Li x Fe3(PO4)2(P2O7), where 0.8≤x≤1; S2, after the sodium source and the precursor are evenly mixed, low-temperature sintering is performed under a reducing atmosphere to obtain a bulk material; S3, washing the bulk material to remove impurity ions, and then performing solid-liquid separation, drying and low-temperature heat treatment to obtain the sodium positive electrode material Na 4-a Li a Fe3(PO4)2(P2O7), where the value of a is 0~0.
3.
2. The method for recycling lithium iron phosphate into sodium positive electrode material according to claim 1, characterized in that: In step S1, the rotation speed of the ball milling activation is 100-200 rpm; In step S1, the ball milling activation time is 0.5 to 3 hours.
3. The method for recycling lithium iron phosphate into sodium positive electrode material according to claim 1, characterized in that: In step S1, the sintering temperature is 300-550° C., and the sintering time is 5-12 hours.
4. The method for recycling lithium iron phosphate into sodium positive electrode material according to claim 1, characterized in that: The phosphorus source is one or more of diammonium phosphate, ammonium phosphate, lithium dihydrogen phosphate, sodium pyrophosphate, ammonium pyrophosphate, and phosphoric acid; The iron source is one or more of ferric nitrate and its hydrate, ferric oxide, ferric phosphate, ferrous oxide, ferric hydroxide, and ferric pyrophosphate; The waste lithium iron phosphate material, the phosphorus source and the iron source are mixed in a molar ratio of Li to total Fe and total P of 0.8 to 1:3:4; The waste lithium iron phosphate material is lithium iron phosphate black powder.
5. The method for recycling lithium iron phosphate into sodium positive electrode material according to claim 1, characterized in that: In step S2, the temperature of the low-temperature sintering is 300-550°C; the time of the low-temperature sintering is 1-15 hours; in step S2, the reducing atmosphere is a mixed atmosphere of argon and hydrogen.
6. The method for recycling lithium iron phosphate into sodium positive electrode material according to claim 1, characterized in that: The ratio of the molar amount of Na contained in the sodium source to the molar amount of the precursor is 5 to 10:1; The sodium source is one or more of sodium acetate and its hydrate, nitrate and its hydrate, carbonate and hydroxide.
7. The method for recycling lithium iron phosphate into sodium positive electrode material according to claim 1, characterized in that: In step S3, the temperature of the low temperature heat treatment is 300-550° C.; the time of the low temperature heat treatment is 5-12 hours; and the atmosphere of the low temperature heat treatment is a protective gas atmosphere.
8. The method for recycling lithium iron phosphate into sodium positive electrode material according to claim 1, characterized in that: In step S2, the mixing is grinding mixing; the grinding mixing is mechanical grinding or manual grinding; the manual grinding time is 0.5 to 2 hours, and the manual grinding is carried out under vacuum or protective atmosphere; the mechanical grinding is grinding for 0.5 to 2 hours after adding a dispersant.
9. A sodium positive electrode material, wherein the chemical formula of the sodium positive electrode material is Na 4-a Li a Fe3(PO4)2(P2O7), wherein the value of a is 0~0.3, characterized in that: The method is prepared according to any one of claims 1 to 8.
10. A sodium ion battery, characterized in that Comprising the sodium positive electrode material as described in claim 9.
Citation Information
Patent Citations
Method for preparing sodium-ion battery positive electrode material from waste lithium iron phosphate
CN116495716A
Method for preparing battery-grade lithium carbonate by recycling lithium iron phosphate battery powder
CN117163979A
Method for synthesizing ferric sodium pyrophosphate positive electrode material by using ferric phosphate
CN118062820A
Closed loop process for near zero-energy regeneration of electrodes by recycling spent rechargeable lithium batteries
US20230207894A1